Sobre divisores livres homogêneos - Silva, Mauri Pereira da (2015)
The maingoalofthisdissertationisthepresentationofconcepts,examplesand characterizations{bothclassicalandrecent{concerningtheimportantandin uential theory oftheso-called freedivisors in thestandardhomogeneouscase.Tothisend,we beginwithabasicstudyonderivationsandwefocusonthemoduledubbed tangential idealizer of agivenhomogeneouspolynomial,whichgeometricallycorrespondstothe moduleoflogarithmicvector eldsalongthegivenprojectivehypersurface(thedivisor is saidtobe free if suchmoduleisfreeoverthegradedpolynomialring).Wewillalso discuss, inparticular,resultsaboutfreedivisorsintheprojectiveplane.